3x-9=75-9x

Simple and best practice solution for 3x-9=75-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-9=75-9x equation:


Simplifying
3x + -9 = 75 + -9x

Reorder the terms:
-9 + 3x = 75 + -9x

Solving
-9 + 3x = 75 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-9 + 3x + 9x = 75 + -9x + 9x

Combine like terms: 3x + 9x = 12x
-9 + 12x = 75 + -9x + 9x

Combine like terms: -9x + 9x = 0
-9 + 12x = 75 + 0
-9 + 12x = 75

Add '9' to each side of the equation.
-9 + 9 + 12x = 75 + 9

Combine like terms: -9 + 9 = 0
0 + 12x = 75 + 9
12x = 75 + 9

Combine like terms: 75 + 9 = 84
12x = 84

Divide each side by '12'.
x = 7

Simplifying
x = 7

See similar equations:

| 2(x+6)=5x+9 | | (21+10)-9j=-277 | | 0=x^2+38x | | 8-10x=6x+1 | | 9x+3-10=3(3+x) | | 1=a(0+b)(0-7.1) | | ln(x)=3.78 | | 23=3p+1 | | 8x=11y | | 4n+38=-3(n-1) | | 2x+14=-4x-19 | | -3(3z+3)*3z=-53 | | -2+5w-7+9=-7 | | -3(2t-2)+4t=7t-7 | | -3(3z+3)+3z= | | 4y+7-y=10y+3y | | n+(n+1)+(n+2)=171 | | 30+0.25*n=59.50 | | y=3x+49 | | (5x+3)(4x-3)=0 | | 2n+5y+5n-6y-2n= | | 3f-12=3[f-12] | | 3c=6+2c | | 15.25d+9.50d+40=213.25 | | 3(2-0.9h)+(-1.3-4)= | | 1=0.1408450704b-1(0-b)(0-7.1) | | -10x+5x+40=90 | | (48-18)+5x=48 | | 0.20(y-9)+0.10y=0.14y-0.05(20) | | -144=11x | | 8x-5=2x-4 | | 8(-7-8n)=16+8n |

Equations solver categories